Development of Controversial Issues Learning Models in Improving Student's Critical Thinking Skills - Raharjo; Etin Solihatin; Moh. Maiwan; Yuyus Kardiman (Studies in Learning and Teaching, 2023)
This research aims to develop a learning model for controversial issues in Civic Education at Jakarta State University to enhance students' critical thinking skills. The study follows the Development and Research (R&D) method and was conducted from March to August. The participants were students taking the Civic Education course at The State University of Jakarta, which is a mandatory course. Data on critical thinking skills were collected through observation, interviews, and assessments. The development of the learning model for controversial issues in the Civic Education course involved planning, processing, designing, material preparation, trials, and feasibility analysis. The research resulted in an efficient and effective learning model. Students' critical thinking skills and learning outcomes improved significantly, as observed through their active participation in discussions, analysis, and argumentation related to controversial issues. Students responded to these issues based on facts and data, thereby demonstrating their improved ability to engage in critical thinking. Overall, this research contributes to the enhancement of critical thinking skills among students by providing them with a structured learning model that enables them to analyze and respond to controversial issues based on reliable information.